Pollen morphological traits analysis of eighteen ’Nepeta’ species in Iran - Talebi, Seyed Mehdi; Nahooji, Majid Ghorbani; Yarmohammadi, Mahbobeh; Azizi, Narjes (Mediterranean Botany, 2020)
Nepeta is one of the largest genera of Lamiaceae, which is widely distributed in Iran. Several species of the genus are traditionally used as culinary, industrial, and medicinal plants. In the present study, we examined fourteen qualitative and quantitative pollen morphological characters of twenty-four populations of eighteen Nepeta using light and scanning electron microscope. The pollen grains are radially symmetric, isopolar, and hexacolpate in all species. We have found that the quantitative features vary among the studied taxa. According to PCA analysis, the colpus length and width are the most variable traits. Polar view shapes in all the studied taxa are circular, while the equatorial view is prolate-spheroidal, subprolate, perprolate, and prolate. We determined microreticulate and bireticulate exine sculpturing, and the bireticulate type was dominant. We revealed that polar and equatorial axes length of pollen grains varied between populations of the same species, and they, therefore, should be ignored in taxonomical identification of species. The polar view was similar in all the studied pollen grains and could not be considered as a diagnostic trait. The equatorial shape was stable between populations of the same species, and this was taxonomically important, while we registered some infraspecific variations in exine sculpture. Our cluster of taxa based on the pollen morphology is not in concordance with the traditional sectional classification of the genus.